Sialoglycoprotein isolated from the eggs of Gadus morhua enhances fracture healing in osteoporotic mice. Issue 3 (6th February 2017) - Zhan, Qiping; Gui, Xiong; Wang, Fei; Yu, Peng; Zhao, Meihui; Wang, Jingfeng; Xue, Changhu
Abstract : Osteoporosis is a common disease in the elderly, which is related to fracture healing delay. Abstract : Osteoporosis is a common disease in the elderly, which is related to fracture healing delay. In this study, the effects of treatment with sialoglycoprotein isolated from the eggs of Gadus morhua ( Gm -SGP) on tibial fracture healing in ovariectomized (OVX) osteoporotic female C57BL/6J mice for 56 days post-fracture were investigated. The result showed that Gm -SGP treatment significantly increased serum angiogenic factors and bone formation markers on day 5 and 11 post-fracture when compared with the OVX group. In addition, histological results in the Gm -SGP group showed a stronger endochondral ossification, a stronger bony consolidation and a stronger bony callus remodeling capability on day 11, 24 and 35 post-fracture, respectively, in comparison with the OVX group. Meanwhile, micro-computerized tomography revealed that the Gm -SGP group had stronger bony callus remodeling capability as evidenced by higher BV/TV and Tb.N but lower Tb.Sp and shorter lengths of callus maximum cross section than the OVX group on day 24 post-fracture. Besides, the tibial callus bending stiffness was significantly enhanced in the Gm -SGP group as compared with the OVX group on day 56 post-fracture. Moreover, gene expression suggested that Gm -SGP promoted vascular invasion and endochondral ossification on day 11 post-fracture as well as bone formation on day 11 and 24 post-fracture via up-regulating the expression of angiogenesis factors (including VEGF, PDGF and Ang1), entochondrostosis factors (including Col2a1, Aggrecan, Col10a1 and MMP-13) and osteogenesis markers (including Col1a1, BMP-2 and OCN). This research suggests that Gm -SGP significantly improve fracture healing which is delayed by OVX-induced osteoporosis. The present study may contribute to providing important implications for the utilization of Gm -SGP from fish eggs as a functional food to enhance fracture healing.